Synthesis and biological evaluation of 2-aryl-4-aminoquinazolines as antitumor agents - Thanh, Le Nguyen; Giap, Tran Huu; Dung, Nguyen Anh; Mung, Vu Thi; My Hue, Van Thi; Minh Hang, Nguyen Thi; Minh, Chau Van; Cho, Won-Jea (Vietnam Journal of Chemistry, 2015)
Quinazoline is an important pharmacophore, showing many biological activities. Some novel 2-aryl-4-aminoquinazolines were designed from 3-arylisoquinoline-1-amines using bioisostere approach. The 4-aminoquinazoline derivatives were prepared from corresponding quinazolinones in 3 steps. The cytotoxicity of these compounds was evaluated against 4 cancer cell lines including human epidermic carcinoma (KB), hepatocellular carcinoma (Hep-G2),  human lung carcinoma (LU-1) and human breast carcinoma (MCF-7). Quinazolineamine compound 4a showed good antitumor activity on KB cell line.